Determinación de la relación entre los parámetros petrofísicos y de producción mediante un análisis de sensibilidad a cuatro clusters del Campo Imperial (2020)
Due to the high lithological heterogeneity of the reservoir, predicting the productive behavior of wells drilled in this area is a challenge for engineers and geologists working in the field. In addition, the fact that the reservoir is pushed by an active aquifer, which conditions the well in its different stages, in drilling any irruption or proximity to the WOC or an out of phase completion can result in a high water cut in production and during production phase the BSW is a known factor that is directly proportional to time. In order to improve the predictive capability of production of the wells, this thesis aims to identify relationships between the petrophysical and the production parameters, from a sample of wells in the field. Finally, a model of equations was proposed in which from the selected petrophysical parameters it is possible to predict the production parameters evaluated with a degree of certainty.